Impact of number of sleep ultradian cycles on polysomnographic parameters related to REM sleep in major depression: Implications for future sleep research in psychiatry. (March 2020) - Hein, Matthieu; Lanquart, Jean-Pol; Mungo, Anaïs; Hubain, Philippe; Loas, Gwenolé
Highlights: Number of sleep ultradian cycles plays a role in the type of REMS alterations. REMS deficiency is related to sleep ultradian cycles <4. REMS disinhibition is associated with sleep ultradian cycles >4. Intermediate REMS alterations is related to 4 sleep ultradian cycles. These results open new perspectives for future sleep research in psychiatry. Abstract: Given the contradictory data on REMS alterations in major depression, the aim of this study was to empirically demonstrate that based on the number of sleep ultradian cycles, it was possible to highlight different subtypes of major depression characterized by specific patterns of REMS alterations. Demographic and polysomnographic data from 211 individuals (30 healthy controls and 181 untreated major depressed individuals) recruited from the sleep laboratory database were analyzed. Major depressed individuals with sleep ultradian cycles <4 showed alterations consistent with REMS deficiency (non-shortened REM latency as well as decrease in REMS percentage, REMS duration and REMS/NREMS ratio) whereas major depressed individuals with sleep ultradian cycles >4 showed alterations consistent with REMS disinhibition (shortened REM latency as well as increase in REMS percentage, REMS duration and REMS/NREMS ratio). Regarding major depressed individuals with 4 sleep ultradian cycles, their REMS alterations were intermediate to those present in major depressed individuals with sleep ultradian cycles <4 and >4. Thus, in major depressed individuals, the highlighting of this heterogeneity of REMS alterations based on the number of sleep ultradian cycles seems to suggest the involvement of distinct pathophysiological mechanisms and could open new perspectives for future sleep research in psychiatry.